PEREKONOMIAN PARIWISATA ISLAMI TERHADAP PEDAGANG DI KAWASAN MAKAM SUNAN KALIJAGA - Galih Caesario Rahman; Sunan Fanani (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This study aims to figure how is the dynamic or economic condition change caused by the existence of Islamic tourism of Sunan Kalijaga Tomb to stall sellers who most of them are the locals lives around the Islamic tourism of Sunan Kalijaga tomb. The research method used is descriptive case study method. Where the data collection done by interview and observation. In this research, the informant is the parties involved in the tourism activity, which is the seller, the visitor, and the worker around the Islamic tourism of Sunan Kalijaga tomb, Demak District. The data analysis used is data reduction, data presentation, and make a conclusion.The research result suggests that the existence of Islamic tourism of Sunan Kalijaga tomb Demak District brings economical change towards the seller works around. REFERENCESAhmad Izzan, dan Syahri Tanjung. 2006. Referensi Ekonomi Syariah; ayat-ayat Al-Qur’an yang berdimensi ekonomi. Bandung: PT. Remaja Rosdakarya. Cet.1.Arikunto, Suharsimi. 2006. Prosedur Penelitian Suatu Pendekatan Praktik.Jakarta :Rineka Cipta.Bungin, Burhan. 2009. Penelitian Kualitatif. Jakarta: Prenada Media GroupI Gede Pitana dan Putu G. Gayatri. 2007. Sosiologi pariwisata. Yogyakarta : Andi.Mashud, Musta’in. 2006. Metode Penelitian Sosial. Jakarta: Kencana Prenada Media Group.Meyers, Koen. 2009. Panduan Dasar Pelaksanaan Ekowisata. Jakarta: Unesco Office.Nyoman S. Pendit. 2002. Ilmu Pariwisata Sebuah Pengantar. Jakarta : Pradnya Paramita.Sugiyono, 2010. Metode Penelitian Kuantitatif Kualitatif & RND. Bandung: Alfabeta.Yoeti, Oka A. 1987. Pengantar Ilmu Pariwisata. Bandung : Angkasa.http://m.tempo.co/read/news/2015/04/05/116655429/4-sebab-islam-jadi-agama-terbesar-dunia-pada-2070 (di akses pada 28 Oktober 2016)